Мозгоподобные структуры для сбора и автоматизированной переработки бизнес-информации - Чередниченко, Ольга Юрьевна; Янголенко, Ольга Васильевна; Гонтарь, Юлия Николаевна (Consilium LLC, 2015)
В работе рассматриваются проблемы сбора и переработки больших объемов бизнес-информации на предприятии. Сформулирована задача систематизации бизнес-информации с целью повышения ее ценности для принятия решений. Определены основные составляющие процесса систематизации информации. Проанализированы алгоритмы поиска бизнес-информации в веб-пространстве, а также методы ее кластеризации. Предложены интеллектуальные модели поиска веб-источников информации, ее извлечения и кластеризации на основе метода компараторной идентификации.

The given work considers the issues of collection and processing of big volumes of business information at the enterprise. The problem statement of systematization of business information is done in order to increase its value for decision-making. The main processes of information systematization are defined. The algorithms of business information search on the web are analyzed as well as clustering methods. The intelligent models of search of the web sources of information, its retrieval and clustering are suggested based on the method of comparator identification.
Brain-like structures for collection and automated processing of business information
Keywords: систематизация; кластеризация; веб-источники; компараторная идентификация; развитие предприятий; business information; systematization; clustering; web source; comparator identification